Problematika Dalam Implementasi Pembelajaran Tematik Di Madrasah Ibtidaiyah Provinsi Jambi - Kiki Fatmawati; Fadlilah; Feviona Septia Nasti; Mhd Subhan; Poni Septiani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Since the implementation of thematic learning in Madrasah Ibtidaiyah, it has not gone smoothly. This research is to examine further the problems experienced by teachers in Jambi Province Madrasah Ibtidaiyah by using a qualitative approach of case study design. Data collection methods such as interviews, observation and documentation. Teachers' problems in implementing thematic learning are that teachers have not been able to make and design thematic learning plans such as lesson plans, syllabus, prota, prosem etc., teachers do not understand the concept of thematic learning, difficulty teaching various subjects in one theme, lack of teaching materials, teacher limitations in applying learning models in low grades, limited learning media owned and difficulties in classifying student learning outcomes and grouping questions on each theme and teachers also have difficulty in dividing the weight and number of questions on each theme. The results of this study can be used as a reference material for making policies or programs related to solving problems/problems faced by teachers in implementing thematic learning.